99.8k views
1 vote
Log²(x + 5) + log²(x - 5) = log²11​

1 Answer

0 votes

Solution:


log_(2)(x + 5) + log_(2)(x - 5) = log_(2)(11) \\ = > log_(2)(x + 5) (x - 5) = log_(2)(11) \\ = > log_(2)( {x}^(2) - 25) = log_(2)(11) \\ cancel \: \: \: out \: \: \: log_(2) \: \: \: from \: \: \: both \: \: \: sides \\ {x}^(2) - 25 = 11 \\ = > {x}^(2) = 11 + 25 \\ = > {x}^(2) = 36 \\ = > x = √(36) \\ = > x = 6

Answer:

x = 6

Hope it helps.

Do comment if you have any query.

User Mounir Elfassi
by
5.6k points